Evaluation of a vancomycin dosing nomogram in obese patients weighing at least 100 kilograms. - Bowers RD; Cooper AA; Wente CL; Wilson DT; Johnson SW; Drew RH (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Background: There remains variability in both practice and evidence related to optimal initial empiric dosing strategies for vancomycin. Objective: Our primary objective was to describe the percentage of obese patients receiving vancomycin doses consistent with nomogram recommendations achieving targeted initial steady-state serum vancomycin concentrations. Secondary objectives were to describe the primary endpoint in subgroups based on patient weight and estimated creatinine clearance, to describe the rate of supratherapeutic vancomycin accumulation following an initial therapeutic trough concentration, and to describe the rate of vancomycin-related adverse events. Methods: This single-center, IRB-approved, retrospective cohort included adult patients ≥ 100 kilograms total body weight with a body mass index (BMI) >30 kilograms/m2 who received a stable nomogram-based vancomycin regimen and had at least one steady-state vancomycin trough concentration. Data collected included vancomycin regimens and concentrations, vancomycin indication, serum creatinine, and vancomycin-related adverse events. Patients were divided into two cohorts by goal trough concentration: 10-15 mcg/mL and 15-20 mcg/mL. Results: Of 325 patients screened, 85 were included. Goal steady-state concentrations were reached in 42/85 (49.4%) of total patients. Conclusions: Achievement of initial steady-state vancomycin serum concentrations in the present study (approximately 50%) was consistent with the use of published vancomycin dosing nomograms.